Dental implant and fungus ball in the ethmoid sinus. Issue 12 (December 2019) - Lee, D.H.; Yoon, T.M.; Lee, J.K.; Lim, S.C.
Abstract: Dental migration into the ethmoid sinus is extremely rare. Furthermore, it is very unusual that a displaced dental implant is associated with a concomitant fungus ball in the ethmoid sinus. Herein, we report an unusual case of the coexistence of a dental implant and fungus ball in the ethmoid sinus. It appears that this condition has not been reported previously.